Mesoscopic Finite Element Modeling of Concrete Considering Geometric Boundaries of Actual Aggregates. (2nd July 2018) - Jin, Hao; Zhou, Yuliang; Wang, Binglong; Zhou, Shunhua
Abstract : Concrete is nonhomogeneous and comprises aggregate, mortar, and interfacial transition zones at the mesoscopic scale. The aggregate shapes significantly affect the development of microcracks. To deal with the problem of imprecise description of actual aggregate, an innovative method of modeling concrete is proposed in this study considering geometric boundaries of actual aggregate. First, the geometric feature points of the actual gravel aggregates, that is, the shape of the actual aggregate, are obtained by laser scanning. The geometric feature points are then moved randomly in the plane. Using this method, an aggregate library is established based on the actual aggregates. Finally, the front polygons-rear circumcircle conflict and overlap criteria are proposed, which can achieve a rapid placing process of the multicontrol point aggregate. Using this method, numerical uniaxial tensile and three-point bending beam tests are conducted and the results are compared with the round aggregate model. The results indicate that the geometric properties of aggregates have both blocking and guiding effects on crack development. Therefore, the proposed modeling method is better suited for analyzing crack development.